Deepening Our Understanding of Reflective Practice in a Safeguarding Child Protection and Welfare Context. Issue 2 (15th March 2023) - McKeown, Marie-Helene Lafleur; Yeung, Echo Yuet Wah
Abstract : This article aims to develop a deeper understanding of reflective practice (RP) in teams in the context of a systemic approach to child protection. It highlights the inherent dichotomy of reflective practice between the very private nature of reflection and its application to the public arena of professional practice. Six social workers in the London Borough of Ealing participated in semi-structured interviews based on their experience of the structures in place to facilitate team reflections, namely daily Morning Check-in (MC) and weekly Group Supervision (GS) meetings. Findings identified four key themes: first RP as a team learning activity; second, the challenge to provide emotional support through RP within the team, third, the time commitment and last the importance of team stability. The impact on social workers' ability to reflect in their teams is discussed using four dimensions of systemic practice; first, the use of 'self' in social work interventions; second, the 'mentalisation' of the child and their family; third, the 'team around the worker' support and fourth, practitioners' reflective learning. Much more needs to be understood to effectively accommodate the private process of RP within the reality of public organisational life.